The Role of Parents in Disciplining Toilet Training for Children 1-3 Years Old - Wulandari, Novita; Rachmawati, Yeni (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
Understanding and supporting the role of parents in toilet training is crucial, not only for the individual development of the child but also for the overall well-being of the family. This article aims to explore the role of parents in disciplining toilet training. This research employs a qualitative approach with a Systematic Review method. The study draws from books and research articles that discuss the role of parents in disciplining child toilet training. The data analysis method used is thematic analysis, which involves identifying patterns through data collected by the researchers. Based on the research findings and existing theories, it can be concluded that parents play a significant role in the success of toilet training for children. Parents' roles are substantial in guiding, assisting, training, supervising, accompanying, and evaluating. The implications suggest that parents' roles are expected to discipline and assist in controlling the desire to defecate and urinate, reduce the use of disposable diapers, enhance children's motor skills, and foster independence. Thus, the implementation of toilet training progresses smoothly.